Low‐Frequency Weather and the Emergence of the Climate - Lovejoy, S; Schertzer, D (Extreme Events and Natural Hazards: The Complexity Perspective, 2012)
This chapter contains sections titled: Introduction Temporal Scaling, Weather, Low‐Frequency Weather, and the Climate Climate Change The Transition From Low‐Frequency Weather to the Climate Temporal Spectral Scaling in the Climate Regime: 10–105 Years Conclusions